Mediation Function of Desired Quality of Life Between Place-Making and Liveable Communities in African Cities - Samuel Medayese; Hangwelani Magidimisha Chipingu; Lovemore Chipungu (Forum Geografi, 2021)
The challenges which confront urban spaces in developing countries have become so enormous, and they continue to challenge the capacity of States in these countries to respond effectively. These challenges range from poor infrastructure to weak infrastructure governance systems, which has created urban liveability differentials within these Cities across Africa. Therefore, this paper examines the mediation role of Desired Quality of life between Place-making and Liveable communities in Africa using a partial least squares path analytic method. This study employed the use of a questionnaire to investigate the desired Quality of life criteria, the place-making preferences, and the focus of liveable communities within these African Cities through an online Google form survey, posted through social media outlets to different respondents across various cities in Africa. The Snowball technique was employed to achieve sampling of 390 respondents across Africa. The responses obtained were synthesized and analyzed using a path analytic approach; the paper examines the relationship between the study's constructs. The data analysis findings show that place-making indeed influences Liveable communities, and Desired Quality of life mediates the relationship between place-making and liveable communities. The results indicate that Cities that prioritize Quality of Life and place-making have better liveable community spaces over those that do not. The study findings have implications for Liveable communities, as it could help city development planners to acknowledge the influence of Quality of life on Placemaking and liveable communities. The study contributes to the current debate on measuring urban Livability within the African City Space by creating a set of desired indicators that suit the African setting's needs regarding City infrastructure planning and provision.